Search for a heavy vector resonance decaying to a Z boson and a Higgs boson in proton-proton collisions at √s=13TeV; European Physical Journal C; Vol. 81, iss. 8 - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Babaev A. A. Anton Anatoljevich; Yuzhakov A. D. Aleksandr Dmitrievich; Okhotnikov V. V. Vitaly Vladimirovich; Sukhikh L. G. Leonid Grigorievich (2021, 2021)
Title screen